PERILAKU SOSIAL BUDAYA POLITIK DAN AKTIVITAS RELIGI MASYARAKAT INDONESIA - Zuhroh, Ni'matuz (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
In order to achieve the authority cannot be separated from political culture in society, political culture according Ranney, there are two main components of political culture, namely cognitive orientations and affective orientations. Meanwhile, Almond and Verba more comprehensive reference on what formulated by Parson and Shils about classification of orientation types, that political culture contains three components as follows: cognitive orientation, affective orientation, and evaluative. In Indonesia also has various religions including Islam, Christian, Hindu, Buddha, and Konghucu. Sometimes, some people believe to witchcraft. Belief /religion of Indonesia people star from the simplest, for example fetishism, animism, pragmatism, and totemism. Belief and religion do not look traditional and modern societies even in Australia, America, and Africa totemism is a system that occupies the position as a religion and become the basis of social organization. J.G. Frezer in Totemism and Exogamy (1910)Keywords: Political culture, System of Religion, and Witchcraft